Attractivité économique des investissements directs étrangers en zone CEMAC : harmonisation des instruments juridiques aux règles internationales - Memphil Ndi, Evelyne Patience (Université de Nice Sophia-Antipolis, 2015)
Les courants de la mondialisation des marchés, marqués par la libre circulation des capitaux et le phénomène du libre-échange ont favorisé la mise en œuvre de politiques communautaires de relance économique et d’attractivité des territoires. C’est dans cette lancée que des regroupements géographiques à visée économique comme la Communauté Économique et Monétaire de l’Afrique Centrale (CEMAC) sont apparus. Six pays de l’Afrique Centrale dont le Cameroun, le Congo, le Gabon, la Guinée Equatoriale, la République Centrafricaine et le Tchad en sont membres et font l’objet de notre analyse sur l’attractivité économique de l’investissement Direct étranger (IDE) dans cette sous-région. L’IDE est devenu un acteur incontournable du processus de développement, et la zone CEMAC une destination privilégiée pour les investisseurs. Il apparait néanmoins une ambiguïté dans les rapports entre le flux d’IDE, la croissance économique et le développement des pays membres de la CEMAC : le taux sans cesse croissant des flux d’IDE entrants dans la sous-région, n’est malheureusement pas toujours synonyme de croissance économique. Pour comprendre ce paradoxe, l’on procède à une analyse des instruments encadrement de l’IDE dans la sous-région CEMAC. Il en ressort que, pour un rendement optimal de ces dispositifs et la garantie d’une croissance économique à long terme dans ces États, il est nécessaire d’associer les politiques actuelles d’attractivité économique des IDE, à une diversification des domaines économiques exploitables , mais aussi adapter les standards internationaux aux spécificités socioculturelles mais aussi économiques de la sous-région CEMAC. The currents of the globalization of the markets, marked by the free movement of capital and the phenomenon of free trade supported the implementation of Community policies of economic revival and attractivity of the territories. It is in this impetus that geographical regroupings with economic aiming like the Economic community and Monetarist of Central Africa (CEMAC) appeared. Six countries of Central Africa of which Cameroon, Congo, Gabon, Equatorial Guinea, the Central African Republic and Chad are members and are for it, the object our analysis on the economic attractivity of direct foreign investment (FDI) in this under-area. The FDI became an inevitable actor of the development process, and CEMAC zones, a privileged destination for the investors. It appears nevertheless an ambiguity in the relationship between the flow of FDI, the economic growth and the development of the member countries of the CEMAC : the rate unceasingly crescent of flows of FDI entering the under-area, is unfortunately not always synonymous with economic growth. To understand this paradox, one carries out an analysis of the instruments framing of the IDE under-area CEMAC. This reveals that, for an optimal output of these devices and the warranty of one long-term economic growth in these States, it is necessary to associate the current policies of economic attractivity of the FDI, with a diversification of the exploitable economic domains, but also to adapt the international standards to sociocultural but so economic specificities of under-area CEMAC. The case of the countries of the BRICS can in this respect, being used as illustration for an “other way” of thinking the development.
Keywords: Afrique centrale; Attractivité économique; Communauté Economique et Monétaire de l'Afrique Centrale; Conditions économiques; Economic attractivity; Foreign direct investment; Harmonisation; Harmonization; Investissements directs étrangers; Investissements étrangers

Determinants and Growth Impact of Foreign Direct Investment in West African Economic and Monetary Union (1980-2010) - Laleye, Abimbola Nicaise (University of Lagos, 2015)
This study’s aim is to assess the trends and the macroeconomic determinants of FDI and to estimate its impact on economic growth, using West African Economic and Monetary Union (WAEMU) and its member countries (Benin, Burkina Faso, Cote d’Ivoire, Guinea Bissau, Mali, Niger, Senegal and Togo) as a case study. In order to achieve the objectives of the current study, the panel cointegration method is employed for the period that expands from 1980 to 2010. This method is constituted of three steps: first, running the panel unit root tests; secondly, run the panel cointegration tests to establish a long-run relationship between the included variables; and thirdly, to run the two models of this study. All this is supplemented by Granger causality test in order to determine the direction of causality between the two variables of FDI and economic growth in WAEMU and its member countries. The findings show that: (i) the variables market size, trade openness, human capital, infrastructure development, financial development, macroeconomic stability, exchange rate and political stability are significant determinants of FDI in WAEMU and in its member countries; (ii) not all the variables affect the same way FDI inflows in WAEMU and in each one of the WAEMU member countries; (iii) there is a positive relationship between FDI and economic growth which implies that FDI stimulates economic growth in WAEMU and its member countries; (iv) this study finds a causality relationship between FDI and economic growth, which runs from FDI to economic growth not from economic growth to FDI: meaning there is a unidirectional linkage between FDI and economic growth in WAEMU; (v) the study also finds that at cross-sectional level, FDI only causes economic growth, not the opposite: this implies that there is also a unidirectional linkage between FDI and economic growth in each WAEMU member country and its runs from FDI to economic growth. Therefore, it is important that the enabling environment should always be provided not only in WAEMU but also in its member countries in order to attract more foreign direct investment and further to stimulate the xiv country’s economic growth. Thus, this study recommends the followings, at the local or country level: first, improvement of the image of WAEMU countries. Rapid economic growth could result in an increase in foreign direct investment inflows, not only in WAEMU but in each one of the WAEMU member countries. But, this has to be done with more attention given to conditions (i.e. key variables) such as fair trade policy with abroad, development of infrastructure and financial system, availability of human capital through a sound human training and formation. At regional or WAEMU level, governments should set up policy that guaranties macroeconomic stability and political stability.
Keywords: Co-integration; Determinants of FDI; FDI; Foreign direct investment; WAEMU; West African Economic and Monetary Union

Policy Options for Promoting Foreign Direct Investment in the Least Developed Countries - Sauvant, Karl P.; Mallampally, Padma (Transnational Corporations Review, 2015)
Foreign direct investment (FDI) plays an important role in the world economy and has the potential to contribute towards accelerating the process of economic growth and sustainable development in the least developed countries (LDCs). The paper provides a brief overview of recent trends and patterns in FDI flows to the LDCs, and then takes stock of the policies, programmes and measures pursued by host and home countries and by international organizations to stimulate FDI flows to LDCs and increase their benefits for these countries. It then lays out a number of policy proposals on how flows to LDCs, and the benefits associated with them, can be enhanced. Finally, it outlines some options for international action to strengthen such efforts – proposals and options that are also relevant to other developing countries.
Keywords: Development; Foreign direct investment; Least Developed Countries; policy options

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

The Investment Treaty Regime and Public Interest Regulation in Ghana: Perspectives in Constitutionalism and General International Law - Dagbanja, Dominic (University of Auckland, 2015)
There is extensive literature on conflict of legal norms and interests in international investment law. The dominant discourse is on the implications of treaty-based investment protection for sovereign regulatory autonomy. Mainstream scholarship critical of the scope and effect of investment treaties has taken the legal status of these treaties for granted. Little systematic attention has been paid to the capacity of states to make investment treaties and the obligations states can or cannot agree to under those treaties in light of their public interest obligations. Yet, this issue is of fundamental importance for three reasons. First, the case for states’ regulatory autonomy arises out of their primary duty to regulate in the public interest. This duty has its legal justification in national constitutions and international law. Second, treaty obligations are founded on the existence of legal norms necessary for the treaty to come into existence and which define the juridical consequences attached to the conclusion of the treaty. These matters are also determined by national constitutions and international law. Third, the limitations inherent in state-specific defences in international investment disputes settlement compel a proactive rethink of the conclusion of investment treaties and how they are interpreted. The question this thesis assesses with reference to Ghana then is: does a state that is legally required to act both under the terms of its constitution and international law in the public interest have the capacity to conclude investment treaties that expressly prevent or abridge the exercise of its public interest regulatory powers, and how should treaties adopted in breach of these obligations be interpreted? To address this question, three areas of public interest regulation that have featured prominently in investment arbitration serve as case studies: the jurisdiction of municipal courts, environmental protection and development policy. Based on the impact and potential limitations of standards of investment protection on these areas, the thesis argues that some treaties are incompatible with the public interest regulation obligations of Ghana under the Constitution and international law. The core proposition of the thesis is that the legal source and public purpose of the State’s powers prevent it from concluding agreements that directly prohibit public interest regulation or indirectly achieve that effect. Accordingly, the thesis proposes that the express and implied limitations on the duty to regulate in the public interest placed on investment treaty making powers of the State must inform the making of investment treaties and their interpretation. By its approach, this thesis establishes a principled basis for reflection on the limits to the State’s capacity to conclude investment treaties and on how they should be interpreted.
Keywords: Ghana; Investment treaty; Investments; Public interest

Harmonising investment laws in the OHADA space - Mugangu, Marie Providence Ntagulwa (University of Cape Town, 2015)
The Organisation for the Harmonisation of Business Law in Africa (OHADA) was established for the purpose of restoring legal and judicial security in the region to attract more investment. The OHADA Treaty included certain areas of business law within its ambit but omitted investment law. There are several laws on investment in the region at the national, regional and sub-regional level that regulate the treatment of foreign investments such as CEMAC and UEMOA investment charters. Moreover OHADA states sign BITs to protect foreign investments. The relationship between the different sub regional laws on investment and OHADA is not yet clear but case law suggests that CEMAC and UEMOA courts recognise the supremacy of OHADA law and their lack of competence to hear matters regulated under OHADA. The standards of protection granted by OHADA states in BITs are very high thus taxing on them. This thesis suggests that OHADA states should either qualify these standards of protection or replace them with more specific provisions. The OHADA system of arbitration cannot effectively settle investment disputes arising out of a BIT leaving international arbitration systems such as ICSID as the best alternative to resolve investment disputes arising out of BITs.
Keywords: International Trade; International Trade Law; Investments

آليات تهيئة مناخ الإسثمار الأجنبي المباشر في الجزائر - بن طراد, أسماء (Ibn Khaldun University of Tiaret, 2015)
تهدف هذه الدراسة إلى استعراض تجربة الجزائر في مجال جذب الاستثمار الأجنبي المباشر من خلال الإشارة إلى جهودها المبذولة في سبيل تهيئة المناخ الاستثمار لامتلاكها مجموعة من مؤهلات واتخاذها العديد من مزايا التي تأهلها على استقطابه ، إلا أنها مازالت رغم ذلك تصنف ضمن المراتب الأخيرة من طرف الهيئات الدولية نظرا لوجود عدة عوامل تحد في مجملها من تدفق الاستثمارات الأجنبية إليها، لهذا خلصت هذه الدراسة إلى محاولة استعراض مجموعة من الآليات الكفيلة بتهيئة مناخ الاستثمار في الجزائر وجعله يتمتع بالاستقرار والجاذبية على جميع المستويات، وبناء تصور متكامل لعوامل جذب الاستثمار الاجنبي في الجزائر للفترة 1980-2012 ، لمعرفة أثرها على تدفقات الاستثمار الأجنبي المباشر واقتراح معالجات مناسبة لها بما ينعكس بالإيجاب عليها مستقبلا.
Keywords: Algérie; Climat d'investissement; Environnement des affaires; FDI; Foreign direct investment; Investissement direct étranger; Investments